PRESERVING JAVANESE CULTURAL WISDOM THROUGH POP MUSIC: A LYRIC ANALYSIS OF NDARBOY GENK’S SONGS - Muntaha Muntaha; Irwan Rohardiyanto; Novianni Anggraini (2025)
This study investigates the role of contemporary Javanese pop music in preserving and transmitting Javanese cultural wisdom, focusing on the works of Ndarboy Genk, a prominent figure in the Javanese modern music scene. The research analyzed the lyrical content of 25 songs written and performed by Ndarboy Genk, including widely recognized tracks such as Wong Sepele, Balungan Kere, Anak Lanang, and Koyo Jogja Istimewa. Using qualitative content analysis supported by theories of cultural preservation and popular discourse, the study examined how traditional Javanese values were embedded and communicated through his lyrics. The findings revealed that Ndarboy Genk’s songs encapsulated a wide range of local wisdom values that reflect Javanese culture's philosophical and ethical dimensions. These included nrimo (acceptance), sabar (patience), andhap asor (humility), teguh ati (emotional resilience), tresna sejati (true love), setya (loyalty), eling lan waspada (mindfulness and caution), and kesederhanaan (simplicity). His lyrics effectively transmit these values to listeners, particularly younger generations through emotionally resonant storytelling and culturally nuanced expressions. Despite the modern and often urban musical style, Ndarboy Genk’s works serve a deeper cultural purpose. The study argues that his music functions not only as entertainment, but as a cultural vehicle that sustains and recontextualizes Javanese identity in the face of contemporary social change. This research highlights the potential of popular music as a medium for cultural education and the preservation of intangible local heritage in modern Indonesia.